2014
DOI: 10.1007/s00464-014-3595-6
|View full text |Cite
|
Sign up to set email alerts
|

Probe-based confocal laser endomicroscopy and fluorescence-based enhanced reality for real-time assessment of intestinal microcirculation in a porcine model of sigmoid ischemia

Abstract: In this experimental model, FLER and CLE were more accurate than clinical evaluation to delineate bowel vascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…In a previous experimental study, we have demonstrated the CLE ability to discriminate between perfused and nonperfused areas of the sigmoid colon, based on specific and early intestinal mucosa morphological changes induced by ischemia [10]. A constant and distinctive CLE clue for ischemic sigmoid areas was the hyperpermeability of the enterocytes resulting in a central accumulation of fluorescein giving ''target-like'' images, which semiologically concurs with the increased demarcation of the brush border observed in the small bowel, in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous experimental study, we have demonstrated the CLE ability to discriminate between perfused and nonperfused areas of the sigmoid colon, based on specific and early intestinal mucosa morphological changes induced by ischemia [10]. A constant and distinctive CLE clue for ischemic sigmoid areas was the hyperpermeability of the enterocytes resulting in a central accumulation of fluorescein giving ''target-like'' images, which semiologically concurs with the increased demarcation of the brush border observed in the small bowel, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The arterial blood was tested on a blood gas analyzer (RAPIDLab 1200 Systems, Siemens Healthcare, Germany). The capillary blood drop from the groin was placed on the sensor of the strip of the lactate analyzer EDGE Ò (Apexbio, Taiwan, ROC) [9][10][11]. Local lactatemia of the stomas was measured on capillary blood obtained by puncturing the stoma mucosa on one of the quadrants, according to the randomization order.…”
Section: Systemic and Local (Stoma) Lactatemiamentioning
confidence: 99%
“…Recently, CLE was used to appreciate microcirculation changes of the digestive mucosa during septic shock in the experimental and clinical setting [13]. Our group demonstrated the ability of the Cellvizio ™ system to accurately discriminate between perfused and ischemic areas in a 1-hour model of bowel ischemia [14]. The aim of this experimental study was to evaluate confocal scanning complemented by functional capillary density area (FCD-A) estimation to define the micro-vessel status in a reiterate, long-lasting porcine model of bowel ischemia.…”
Section: Introductionmentioning
confidence: 98%
“…2). In a series of experimental studies [50][51][52][53][54], we were able to demonstrate the accuracy of this technique, which will be soon translated to the clinical setting at the IHU-Strasbourg (Perfusion Evaluation by Real-time Fluorescence-based EnhanCed realiTy of anastomosis: PER-FECT trial).…”
Section: Introductionmentioning
confidence: 99%
“…In rectal surgery, an immediate surgical problem is the potential need to sacrifice the anal sphincter. Confocal laser endomicroscopy (CLE) is a realtime imaging system, which allows for digital ''biopsies'' at micron-level resolution [51]. The probe fits within the working channel of standard flexible endoscopes.…”
Section: Introductionmentioning
confidence: 99%